1989
DOI: 10.1111/j.1525-1594.1989.tb02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Platelet‐Binding Immunoglobulins and Improvement in Platelet Counts in Patients with HIV‐Associated Idiopathic Thrombocytopenia Purpura (ITP) Following Extracorporeal Immunoadsorption of Plasma Over Staphylococcal Protein A‐Silica

Abstract: Platelet-directed antibodies and circulating immune complexes (CIC) were removed from plasma of patients with human immunodeficiency virus (HIV) infection and idiopathic thrombocytopenic purpura (ITP) by extracorporeal immunoadsorption using columns of Staphylococcal protein A-silica (Prosorba columns). In addition, stimulation of a broadly cross-reactive anti-F(ab')2 antibody response was observed. These antibodies also appeared to play a role in the additional removal of platelet-directed immunoglobulins (Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 30 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The extent of the efgartigimod-induced IgG lowering is similar or exceeds the levels of autoantibody reduction achieved with alternative strategies, such as IVIg, plasma exchange, or immunoadsorption, and falls within the range associated with a clear clinical benefit in various autoimmune indications (35)(36)(37). Indeed, reducing the autoantibody levels in myasthenia gravis patients by about 30% using IVIg resulted in a clinical efficacy rate of 40% (35), and this efficacy rate increased to 80% when titers were further lowered by plasma exchange to 60%.…”
Section: Discussionmentioning
confidence: 92%
“…The extent of the efgartigimod-induced IgG lowering is similar or exceeds the levels of autoantibody reduction achieved with alternative strategies, such as IVIg, plasma exchange, or immunoadsorption, and falls within the range associated with a clear clinical benefit in various autoimmune indications (35)(36)(37). Indeed, reducing the autoantibody levels in myasthenia gravis patients by about 30% using IVIg resulted in a clinical efficacy rate of 40% (35), and this efficacy rate increased to 80% when titers were further lowered by plasma exchange to 60%.…”
Section: Discussionmentioning
confidence: 92%
“…with a measurable reduction in the size of adenocarcinoma metastases [ 19,201, and decreased levels of platelet autoantibodies were associated with normalization of platelet counts in patients with ITP [8,[10][11][12][13]201 and C-TTPIHUS [ 141. However, no direct link between removal of specific CIC and modulation of specific antibody responses has been established.…”
Section: Treatment Devicementioning
confidence: 99%
“…The rationale behind the use of such devices is that protein A has greater affinity for the Fc region of immune-complexed immunoglobulin G (IgG) than for monomeric IgG [2-61. Multicenter clinical studies of one such device (PROSORBA@ columns) have demonstrated induction of clinical responses in cancer [ 7 ] , idiopathic thrombocytopenic purpura (ITP) , cancer chemotherapyassociated thrombotic thrombocytopenic purpura/hemolytic uremic syndrome (C-TTP/HUS) [ 1 1,141, and refractory idiopathic TTP patients [ 151. Clinical responses were often correlated with immunologic responses, such as increases in natural killer cell activity, monocyte interleukin-1 (IL-1 ) production, absolute numbers of T-helper and B cells, and antibodies against disease-associated antigens and autoantibodies, and a decrease in the absolute numbers of activated T-suppressor cells [ 13,14,. Certain specific antibody responses were found to correlate with disease status in patients with adenocarcinoma, ITP, or C-TTP/HUS who received immunoadsorption treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the immunoadsorptive plasmapheresis method by using the PROSORBA column has been approved by the FDA for clinical trials. 24,25 Despite some clinical promise, a recent ITP "practice guideline" prepared by a panel of the American Society of Hematology listed Protein-A therapy for refractory ITP patients (i.e., refractory to prednisone and splenectomy) as a low preference therapy compared with IVIG. 1 This low preference given to Protein-A plasmapheresis was apparently attributed to the nonspecific nature of this therapy; all IgG would be extracted from plasma, thereby increasing the patient's susceptibility to opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this method using the PROSORBA column has been approved by the Food and Drug Administration (FDA) for clinical use in treatment of ITP. 19,24,25 The PROSORBA column is made of silica gel containing immobilized Protein-A, a bacterial protein that binds the Fc region of immunogammaglobulin with high affinity. 26 Although this PROSRBA column removes pathological antibodies and immune complexes from the patient, it also depletes protective antibodies, thereby weakening the body's self-defense system and increasing patient susceptibility to opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%